Allocation, not male resistance, increases male frequency during epidemics: a case study in facultatively sexual hosts. Issue 11 (11th October 2017) - Hite, Jessica L.; Penczykowski, Rachel M.; Shocket, Marta S.; Griebel, Katherine A.; Strauss, Alexander T.; Duffy, Meghan A.; Cáceres, Carla E.; Hall, Spencer R.
Abstract: Why do natural populations vary in the frequency of sexual reproduction? Virulent parasites may help explain why sex is favored during disease epidemics. To illustrate, we show a higher frequency of males and sexually produced offspring in natural populations of a facultative parthenogenetic host during fungal epidemics. In a multi‐year survey of 32 lakes, the frequency of males (an index of sex) was higher in populations of zooplankton hosts with larger epidemics. A lake mesocosm experiment established causality: experimental epidemics produced a higher frequency of males relative to disease‐free controls. One common explanation for such a pattern involves Red Queen (RQ) dynamics. However, this particular system lacks key genetic specificity mechanisms required for the RQ, so we evaluated two other hypotheses. First, individual females, when stressed by infection, could increase production of male offspring vs. female offspring (a tenant of the "Abandon Ship" theory). Data from a life table experiment supports this mechanism. Second, higher male frequency during epidemics could reflect a purely demographic process (illustrated with a demographic model): males could resist infection more than females (via size‐based differences in resistance and mortality). However, we found no support for this resistance mechanism. A size‐based model of resistance, parameterized with data, revealed why: higher male susceptibility negated the lower exposure (a size‐based advantage) of males. These results suggest that parasite‐mediated increases in allocation to sex by individual females, rather than male resistance, increased the frequency of sex during larger disease epidemics.